2020
DOI: 10.1111/jvim.15906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antimicrobial stewardship on antimicrobial prescriptions for selected diseases of dogs in Switzerland

Abstract: Background: Antimicrobial stewardship programs (ASPs) are important tools to foster prudent antimicrobial use. Objective: To evaluate antimicrobial prescriptions by Swiss veterinarians before and after introduction of the online ASP AntibioticScout.ch in December 2016. Animals: Dogs presented to 2 university hospitals and 14 private practices in 2016 or 2018 for acute diarrhea (AD; n = 779), urinary tract infection (UTI; n = 505), respiratory tract infection (RTI; n = 580), or wound infection (WI; n = 341). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Elucidation of proportional usage of antibiosis, for example, could provide evidence of a bacterial role in the otitis externa process while evidence from bacterial culture and antimicrobial sensitivity testing could provide deeper insights into the most commonly associated bacteria and their common antibiograms [ 78 , 79 ]. There is also currently high interest in exploring aspects related to antimicrobial stewardship in companion animals and therefore benchmarking of current first opinion therapeutic patterns to offer additional scientific benefits [ 75 , 80 ]. A deeper understanding of breed as a risk factor for otitis externa could take into account the severity of the disorder phenotype experienced by these dogs as well as a range of temporal characteristics including the duration of individual events, recurrence and chronicity.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidation of proportional usage of antibiosis, for example, could provide evidence of a bacterial role in the otitis externa process while evidence from bacterial culture and antimicrobial sensitivity testing could provide deeper insights into the most commonly associated bacteria and their common antibiograms [ 78 , 79 ]. There is also currently high interest in exploring aspects related to antimicrobial stewardship in companion animals and therefore benchmarking of current first opinion therapeutic patterns to offer additional scientific benefits [ 75 , 80 ]. A deeper understanding of breed as a risk factor for otitis externa could take into account the severity of the disorder phenotype experienced by these dogs as well as a range of temporal characteristics including the duration of individual events, recurrence and chronicity.…”
Section: Discussionmentioning
confidence: 99%
“…Lehner et al [ 132 ] conducted the study with the objective to investigate antimicrobial prescriptions by Swiss veterinarians before and after introduction of the online ASP AntibioticScout.ch in December 2016. In the methodology, authors have used a retrospective study, where the prescriptions of antimicrobials in 2016 and 2018 were compared and their appropriateness was assessed by a justification score.…”
Section: Inappropriate Prescribing Of Antibioticsmentioning
confidence: 99%
“…The results of the study revealed that percentage of dogs prescribed antimicrobials decreased significantly between 2016 and 2018, which led to a conclusion that antimicrobials were used more carefully. The study highlights the continued need for ASPs in veterinary medicine [ 132 ].…”
Section: Inappropriate Prescribing Of Antibioticsmentioning
confidence: 99%
“…Moreover, this system can suggest outcomes of the prescription and consumption of antimicrobial drugs, divided by species, pathology, apparatus, and type of drugs. The papers of Lehner et al [ 23 ] and Hubbuc et al [ 15 ] demonstrated that, in Switzerland, the introduction of the online antimicrobial stewardship program, which gives advice/recommendations, significantly decreased the prescription of antimicrobials for UTIs in dogs and cats. In the complex context of ASP, this kind of tool could be enrolled among “educational” tools.…”
Section: Discussionmentioning
confidence: 99%